Research on Fine‐Grained Phenotypic Analysis of Temporal Root Systems – Improved YoloV8seg Applied for Fine‐Grained Analysis of In Situ Root Temporal Phenotypes - Qiushi Yu; Meng Zhang; Liuli Wang; Xingyun Liu; Lingxiao Zhu; Liantao Liu; Nan Wang (Advanced Science)
Abstract Root systems are crucial organs for crops to absorb water and nutrients. Conducting phenotypic analysis on roots is of great importance. To date, methods for root system phenotypic analysis have predominantly focused on semantic segmentation, integrating phenotypic extraction software to achieve comprehensive root phenotype analysis. This study demonstrates the feasibility of instance segmentation tasks on in situ root system images. An improved YoloV8n‐seg network tailored for detecting elongated roots is proposed, which outperforms the original YoloV8seg in all network performance metrics. Additionally, the post‐processing method introduced reduces root identification errors, ensuring a one‐to‐one correspondence between each root system and its detection box. The experiment yields phenotypic parameters for fine‐grained roots, such as fine‐grained root length, diameter, and curvature. Compared to traditional parameters like total root length and average root diameter, these detailed phenotypic analyses enable more precise phenotyping and facilitate accurate artificial intervention during crop cultivation.